K-drama Binge Watching among College Students: Motives, Patterns and Implications - Aunul, Sofia; Handoko, Daniel; Riswandi, Riswandi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The binge-watching phenomenon has become a trend when one of the online streaming television platforms, Netflix, offers a variety of series genres. The phenomenon of binge-watching has become a common practice among spectators and students are one of them and binge-watching activities are part of student activities in their daily lives. This study aims to describe the motives, patterns and implications of binge-watching through descriptive qualitative approach using interview in obtaining primary data with 20 college students as informants. The results of the study found that there are (1) the motivation of students to binge-watch is to spend time, entertain, escape, and relax (2) the implications of watching marathons are in the form of physiological and social implications.